Loss of VAPB Regulates Autophagy in a Beclin 1-Dependent Manner - Wu, Dan (Neurosci Bull, 2018)
Autophagy is an evolutionarily-conserved self-degradative process that maintains cellular homeostasis by eliminating protein aggregates and damaged organelles. Recently, vesicle-associated membrane protein-associated protein B (VAPB), which is associated with the familial form of amyotrophic lateral sclerosis, has been shown to regulate autophagy. In the present study, we demonstrated that knockdown of VAPB induced the up-regulation of beclin 1 expression, which promoted LC3 (microtubule-associated protein light chain 3) conversion and the formation of LC3 puncta, whereas overexpression of VAPB inhibited these processes. The regulation of beclin 1 by VAPB was at the transcriptional level. Moreover, knockdown of VAPB increased autophagic flux, which promoted the degradation of the autophagy substrate p62 and neurodegenerative disease proteins. Our study provides evidence that the regulation of autophagy by VAPB is associated with the autophagy-initiating factor beclin 1.